Cost-effectiveness and Clinical Outcomes of Early Anti–Tumor Necrosis Factor–α Intervention in Pediatric Crohn's Disease. Issue 8 (15th November 2019) - Bashir, Naazish S; Walters, Thomas D; Griffiths, Anne M; Ito, Shinya; Ungar, Wendy J
Abstract: Background: Anti–tumor necrosis factor–α (anti-TNF-α) treatments are increasingly used to treat pediatric Crohn's disease, even without a prior trial of immunomodulators, but the cost-effectiveness of such treatment algorithms has not been formally examined. Drug plan decision-makers require evidence of cost-effectiveness to inform funding decisions. The objective was to assess the incremental cost-effectiveness of early intervention with anti-TNF-α treatment vs a conventional step-up strategy per steroid-free remission-week gained from public health care and societal payer perspectives over 3 years. Methods: A probabilistic microsimulation model was constructed for children with newly diagnosed moderate to severe Crohn's disease receiving anti-TNF-α treatment and concomitant treatments within the first 3 months of diagnosis compared with children receiving standard care consisting of steroids and/or immunomodulators with the possibility of anti-TNF-α treatment after 3 months of diagnosis. A North American multicenter observational study with 360 patients provided input into clinical outcomes and health care resource use. Results: Early intervention with anti-TNF-α treatment was more costly, with an incremental cost of CAD31, 112 (95% confidence interval [CI], 2939–91, 715), and more effective, with 11.3 more weeks in steroid-free remission (95% CI, 10.6–11.6) compared with standard care, resulting in an incremental cost per steroid-free remission-week gained of CAD2756 from an Ontario public health care perspective and CAD2968 from a societal perspective. The incremental cost-effectiveness ratio was sensitive to the price of infliximab. Conclusions: The results suggest that although early anti-TNF-α was not cost-effective, it was clinically beneficial. These findings, along with other randomized controlled trial evidence, may inform formulary decision-making. Abstract : Intervention with anti-TNF-α within 3 months of diagnosis in pediatric CD results in 11.3 additional weeks of steroid-free remission over 3 years compared with step-up care, but is costly, with an incremental cost per steroid-free remission-week gained of CAD2756.